Preimplantační genetická diagnostika chromosomálních abnormit embryí – realita a budoucnost - Veselá, Kateřina (1. mezinárodní andrologický kongres v České republice, 2006)
Since 1994, when the first paper was published by Harper and Handyside summarizing the world experience of PGD, this method became a routine procedure both in precise diagnostic and therapy of infertility. The vast majority of PGD cycles for the chromosomal abnormity are performed with the major indication being aneuploidy. Nevertheless the number of PGD cycles for structural rearrangements are also growing up. Methods: The occurrence of non-disjunction during meiosis is a quite rare event in most organisms with the exception of the human species where approximately a half of oocytes and a tenth of spermatozoa carry chromosomal abnormity. In addition, other possible causes of chromosomal aneuploidy are considered, e.g. the dysfunction of the spindle during early mitosis. Results: The group of indications for PGD and PGD-AS (aneuploidy screening) is dynamically expanding, and the growing experience in PGD is generating a daunting myriad of innovations in assisted reproductive techniques and turns dramatically the angle of a view to a general concept on human infertility. Conclusions: The strengthening tendency to enlargement the numbers of PGD cycles is awaited for the future decade with the respect to the expected benefits for the clients. New methods simplifying the PGD diagnosis are considered and welcome. 19